How does the ABC lima dasar game improve parent and children communication? - Noor Baiti; Muhammad Zulkarnaen; Sarimah (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This research aims to improve communication between child and parent through the ABC lima dasar game. The research subjects were 15 children aged 5-6 years in Anjir Muara, South Kalimantan. This classroom action research uses the Kemmis-Taggart model for two cycles. Methods of data collection using observation and analysis descriptively. The results showed an increase in children's communication skills with their parents from cycles 1 to 2 to be more effective. Therefore, the ABC lima dasar game has become an alternative game to apply at preschool with parents. The effectiveness of the game if played at home can be studied further.